Development of a multivalent DNA vaccine against pathogenic leptospiral infection in laboratory animal model - Bashiru, Garba (2017)
Leptospirosis is neglected emerging zoonoses, occurring both in urban environments as well as rural regions worldwide. During occupational and recreational activities, humans that come in direct contact with infected animals or environments contaminated by the urine of reservoir animals are at a higher risk of infection. Prevention is basically through improved hygienic measures and rodent control which is very difficult to achieve particularly in developing countries. Development of an effective vaccine against leptospirosis remains a challenge. The heat-killed whole-cell vaccine has been seen to produce some undesirable side effects which include pain, nausea and fever, short term immunity and serovar restricted protection. Multi-epitope peptide DNA vaccines are effective against some viruses and they have recently been shown to have potential efficacy against some bacterial diseases including leptospires. They are also known mimic antigen processing and presentation during natural infection and can induce more potent immunoreaction than the whole protein vaccine. The aim of this study is to develop a multivalent DNA vaccine that can stimulate significant antibody production that will aid the control and prevention of leptospirosis using hamster model. Antigenic B cell epitopes from highly conserved leptospiral genes LipL32, LipL41, OmpL1, Loa22 and LigA were predicted using bioinformatics tools, assembled and linked using Gly-Ser spacer and chemically synthesized. The vaccine constructs were composed of the lipopolyscharide genes (LipL32, LipL41), the outer membrane porin and outer membrane-like protein (OmpL1, Loa22), the immunoglobulin-like protein (LigA) and the final construct that is a combination of all the other constructs. The synthesized DNA was cloned in a pBudCE4.1 mammalian expression vector. The multivalent DNA(s) were expressed (invitro) and confirmed by indirect immunofluorescence antibody test. The indirect immunofluorescence test showed that the recombinant protein was expressed in CHO-K1 cells and it reacted with antibodies against the V5 and Myc epitope tags fused to the cloned expression plasmid vector at the 5’ end of the constructs. To evaluate the efficacy of the DNA vaccines, 3-4 weeks old golden Syrian hamsters were immunized with 150μg of the vaccine in equal volume of incomplete Freund’s adjuvant. Subsequently, all the hamster groups were challenged with L. interrogans Copenhageni Fiocruz strain except the control group. Analysis of humoral immune response by microscopic agglutination tests showed agglutinating antibodies production (p<0.05) by the immunized hamsters and the antibodies were immunologically cross-reactive with a range of reference pathogenic leptospira strains including L. interrogans, L. borgpetersenii, L. weilii, L. santorasai belonging to different serogroups. Similarly, all the vaccines were able to stimulate secretion of neutralizing antibodies that prevented the growth of a number of pathogenic leptospira species as indicated by the invitro growth inhibition test using a panel of 19 serovars. Histopathological evaluation of kidneys of challenged hamsters showed that the vaccine significantly reduced kidney colonization by the leptospires as indicated by the moderate to severe pathological lesions observed in the kidney tissues. In conclusion, the multi-epitope chimeric DNA vaccine proves to be a promising antigen for the prevention of renal colonization and urinary shedding of the bacteria, which is the major contributing factor for the persistence of the bacteria in susceptible animals as well as as the environment. It also showed great potential for stimulation of cross-reactive immunity against a broad range of pathogenic leptospira serovars.